Gender dalam Perspektif Hadis Maudhu’i - Rusdaya Basri (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
This article examined the controversy of women's testimony and leadership between normative and substantive meanings based on Islamic legal agreements. Hadith about women's testimony of half men's testimony in the terms of law must be reviewed through socio-history. In hermeniotic perspective, the verse about testimony must be seen as a response to the historical facts at the time this verse came down. Thus, compiling historical facts has changed, it can be done to reinterpret the verses and hadith. The hadith about women's leadership in politics in terms of sanad is valid but the understanding of hadith must be approached based on sosio history because the matan of hadith is not always factual. This hadith was conveyed in response to the news of the appointment of Kisra's daughter, a woman who did not receive social approval from the community so that the hadith was acceptable only locally and temporally, not universally applicable. Therefore, leadership in politics can be carried out by anyone, male and female, as long as he/she gain legitimacy from the community.